Access to adequate menstrual hygiene management by school going girls as a human right in Zimbabwe - Durojaye, Ebenezer (University of Pretoria, 2025)
Mini Dissertation (LLM (Sexual and Reproductive Rights in Africa))--University of Pretoria, 2024.